JACIE - A scripting language for Internet-based multimedia collaborative applications. - Abdul Samad Haji-Ismail (2001)
"The Internet has opened the opportunity for geographically dispersed computer users to concurrently interact, collaborate and socialise in a virtual group environment. It has shifted the nature of Internet users from "individualistic net-surfers" to "active collaborative teamworkers". But developing Internet-based collaborative applications is very laborious, tedious and time consuming. Besides patience, knowledge and skill in low-level network programming are required especially for managing interactions and communications. This thesis presents a research on the construction of a development tool for collaborative multimedia applications. The tool, named JACIE (Java-based Authoring language for Collaborative Interactive Environments), is a script language which has been developed to support rapid implementation of a wide range of network-based interactive and collaborative applications. In particular, it facilitates the management of interaction and communication through simple communication primitives such as channels and interaction protocols, hence hiding much network programming from programmers. JACIE also features a template-based programming style, a single program for both client and server, and platform-independence by using Java as the target language. A compiler prototype has been developed that translates JACIE codes to Java. Several sample applications have been implemented in JACIE and are discussed in the thesis. The major research contribution is a high-level abstraction language for collaborative multimedia applications that simplifies many programming tasks. JACIE can be a useful multimedia software engineering tool well-suited for a wide range of collaborative applications, be they stand-alone client/server applications or Web-based client/server applets."